Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1186/1471-2369-13-34
|View full text |Cite
|
Sign up to set email alerts
|

Kidney biopsy in patients with glomerulonephritis: is the earlier the better?

Abstract: BackgroundInterventional diagnostic procedures are established for several diseases in medicine. Despite the KDOQI guideline recommendation for histological diagnosis of kidney disease to enable risk stratification, its optimal time point has not been evaluated. We have therefore analyzed whether histological diagnosis of glomerulonephritis (GN) at an early stage of chronic kidney disease (CKD) is associated with different outcome compared to diagnosis at a more advanced stage.MethodsA cohort of 424 consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
2
0
4
Order By: Relevance
“…A previous study 15 showed that early guidance of renal biopsy may confer significant benefits in preserving renal function in patients. Compared with other patients, patients with CKD stages 1 and 2…”
Section: Discussionmentioning
confidence: 99%
“…A previous study 15 showed that early guidance of renal biopsy may confer significant benefits in preserving renal function in patients. Compared with other patients, patients with CKD stages 1 and 2…”
Section: Discussionmentioning
confidence: 99%
“…Although is commonly accepted that glomerular haematuria indicates GFB dysfunction, its usefulness as glomerular injury marker is not properly established and so it is not formally included as a biopsy criterion in the KDIGO Clinical Practice Guidelines 20 . Similarly, although it has been suggested that early identification of glomerular disease optimizes treatment and may be beneficial on early CKD stages there is no consensus on whether biopsy should be performed in patients with haematuric glomerular diseases 21 22 . Recent evidences reported that persistent isolated haematuria increased 18-fold the risk of ESRD 9 , mainly due to primary glomerular diseases, pointing that persistent mH could be an early feature of glomerulonephritis.…”
Section: Discussionmentioning
confidence: 99%
“…Согласно клиническим и практическим рекомендациям Научного общества нефрологов России (НОНР) морфологическая диагностика ОГН базируется на данных световой и электронной микроскопии, а также иммунофлюоресцентного исследования биоптата почек [17,18,48]. При световой микроскопии отмечается увеличение клубочков, сужение их просвета за счет пролиферации мезангиальных клеток, увеличение толщины мезангиального матрикса, большое число нейтрофильных лейкоцитов, сужение просвета капилляров клубочков [48,49]. Для ОПСГН характерна картина эндокапиллярного пролиферативного гломерулонефрита [47,50].…”
Section: этиопатогенез и морфологические измененияunclassified
“…При электронной микроскопии можно обнаружить субэпителиальные депозиты (иммунные комплексы) по типу «горбов». Формирование полулуний при ОГН считается прогностически неблагоприятным вариантом заболевания [49,50]. При иммунофлюоресцентном исследовании типичным признаком является обнаружение гранулированных депозитов иммуноглобулина G и C3-комплемента в мезангии и стенках капилляров клубочков [49,50].…”
Section: этиопатогенез и морфологические измененияunclassified
See 1 more Smart Citation